Isolation and characterization of Pulp from sugarcane bagasse and rice straw - Suhardy, Daud; Farhana Diyana, Mohd Yunos; Farizul Hafiz, Kasim; Saiful Azhar, Saad; Harbant, Singh (Universiti Malaysia Perlis, 2009)
The amount of sugarcane bagasse and rice straw in the state of Perlis (Malaysia) is abundant while its utilization is still limited. One of the alternatives for the bagasse and straw utilization is as pulp raw material. This paper reviews on pulp from sugarcane bagasse and rice straw and its suitability for paper production. In this study, the pulp was extracted by the Soxhlet extraction method. The objective of this study was to investigate the cellulose, lignin and silica content of the pulp from sugarcane bagasse and rice straw. For rice straw, the presence of large amount of pentosanes in the pulp and black liquors, which also contain silica were decreased the using of straw in the paper industry. Therefore, formic acid pulping and NaOH treatment are studied to reduce or prevent silica. The isolated pulp samples were further characterized by Scanning Electron Microscope (SEM) to investigate their fiber dimensions.